Critical Discourse Analysis on the Texts Dimension of the FIFA President’s Speech: Press Conference of FIFA in Qatar (LITPAM, 2024)
This article examines the text dimension of the President Press Conference of FIFA in Qatar 2022. The objective of the article is to examine the text dimension of the FIFA president's speech at the opening of the FIFA World Cup on November 19th, 2022 by using the theory of Fairclough’s text dimension such as phonology, morphology, syntax, and semantics. This article used a descriptive qualitative method and critical discourse analysis approach. The data were taken from the speech of the 2022 FIFA president's speech. The result revealed that the meaning of the FIFA World Cup president’s speech covered the text analysis dimension. First, in the text analysis dimension, Infantino Gramsci’s speech fulfilled the hierarchy of grammatical structures built completely (phonology, morphology, syntax, and semantics). In the phonology aspect, it is just used as a rhyme rather than alliteration and assonance. In the morphological aspect, it is used various types of inflectional word classes but did not change the meaning in assembling his speech and the aspects of syntax and semantics frequently appeared, however, the president attempted to show that his statements were grammatically precise and that he effectively conveyed the content of his address through the use of semantics. The highlights are that Infantino created patterns in the way he put his phrases together as a speech producer to satisfy the requirements of the speech hierarchy by having a high level of communication proficiency, or, from a linguistic standpoint, spoken language.